THE CORRELATION OF CLASSROOM MANAGEMENT IMPLEMENTATION AND TEACHERS’ TEACHING SKILL TOWARDS STUDENTS’ LEARNING OUTCOMES AT SD INPRES LOKA KECAMATAN ULU ERE KABUPATEN BANTAENG - Jabal Rahmat; Rosleny Babo, Andi Jam’an (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This quantitative type of research aimed to answer the formulation of problems, namely: 1) the implementation of classroom management and its effect on students’ learning outcomes at SD Inpres Loka Kecamatan Ulu Ere Kabupaten Bantaeng, 2) the correlation of teachers’ teaching skills and the students’ learning outcomes at SD Inpres Loka Subdistrict Ulu Ere Kabupaten Bantaeng, 3) the correlation of classroom management and teachers’ teaching skills towards the students’ learning at SD Inpres Loka Kecamatan Ulu Ere Kabupaten Bantaeng. This study was administered by distributing questionnaires and documentation format to a population of 122 students sampled with stratified random sampling proportionate techniques set by 37 students. The data were processed and analyzed with statistical techniques, both descriptive statistics and inferential statistics. Through data analysis, the conclusion was obtained, that 1) the implementation of class management was moderately related at 0.504 with a significance of 0.334 to the students’ learning outcomes at SD Inpres Loka Ulu Ere Kabupaten Bantaeng, 2) teachers’ teaching skills were well related at 0.851 with a significance of 0.334 to the students’ learning outcomes at SD Inpres Loka Kecamatan Ulu Ere Kabupaten Bantaeng, 3) the implementation of classroom management and teachers’ teaching skills were highly related at 6.710 with a significance of 3.520 to the students’ learning outcomes at SD Inpres Loka Kecamatan Ulu Ere Kabupaten Bantaeng.